(untitled) (Research, Society and Development, 2024)
Neonatal hyperbilirubinemia is characterized by increased serum bilirubin levels in the newborn’s bloodstream, reaching a percentage considered high in this population. Phototherapy is one of the most commonly used treatments, being the first therapeutic choice for neonatal hyperbilirubinemia. The objective of the study is to understand the perception of mothers about the care of newborns with hyperbilirubinemia undergoing phototherapy. This is a qualitative, exploratory, descriptive study produced through participatory observation and interviews, analyzed by Bardin’s Thematic Content Analysis. Mothers of newborns with hyperbilirubinemia undergoing phototherapy participated in the study, carried out in a public hospital in the interior of Pernambuco. The result revealed that maternal perceptions become positive or negative in light of what they are experiencing in the diagnosis of neonatal hyperbilirubinemia and phototherapy. Therefore, 3 thematic categories emerged: feelings of mothers of newborns with hyperbilirubinemia undergoing phototherapy; Care provided by mothers of newborns undergoing phototherapy and communication by the health team about care for newborns with hyperbilirubinemia undergoing phototherapy. It is concluded, therefore, that mothers of newborns with hyperbilirubinemia undergoing phototherapy reflect through their perceptions what they are experiencing and the guidance they are receiving and/or the divergence between them.